THE GROUNDS of the INSTITUTIONAL DISCOMPLEMENTARITY of the KNOWLEDGE ECONOMY in the COUNTRIES with TRANSITION ECONOMIES - Соболев, В. М.; Голик, Д. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
The concept of discomplementarity index of institutional factors is introduced. We find correlations between the index value of the knowledge economy and its pillar discomplementarity indexes. We show that East European countries, including Baltic ones, are characterized by positive dynamics, i.e. by the decrement of discomplememtarity indexes and the increment of the knowledge economy indexes. On the other hand, the rest of the former Soviet Union countries have not improved their indexes since 1995.